Comparison of whole genome sequences from human and non-human Escherichia coli O26 strains - Norman, Keri N.; Clawson, Michael L.; Strockbine, Nancy A.; Mandrell, Robert E.; Johnson, Roger; Ziebell, Kim; Zhao, Shaohua; Fratamico, Pina M.; Stones, Robert; Allard, Marc W.; Bono, James L. (Frontiers in Cellular and Infection Microbiology, 2015)
Shiga toxin-producing Escherichia coli (STEC) O26 is the second leading E. coli serogroup responsible for human illness outbreaks behind E. coli O157:H7. Recent outbreaks have been linked to emerging pathogenic O26:H11 strains harboring stx2 only. Cattle have been recognized as an important reservoir of O26 strains harboring stx1; however the reservoir of these emerging stx2 strains is unknown. The objective of this study was to identify nucleotide polymorphisms in human and cattle-derived strains in order to compare differences in polymorphism derived genotypes and virulence gene profiles between the two host species. Whole genome sequencing was performed on 182 epidemiologically unrelated O26 strains, including 109 human-derived strains and 73 non-human-derived strains. A panel of 289 O26 strains (241 STEC and 48 non-STEC) was subsequently genotyped using a set of 283 polymorphisms identified by whole genome sequencing, resulting in 64 unique genotypes. Phylogenetic analyses identified seven clusters within the O26 strains. The seven clusters did not distinguish between isolates originating from humans or cattle; however, clusters did correspond with particular virulence gene profiles. Human and non-human-derived strains harboring stx1 clustered separately from strains harboring stx2, strains harboring eae, and non-STEC strains. Strains harboring stx2 were more closely related to non-STEC strains and strains harboring eae than to strains harboring stx1. The finding of human and cattle-derived strains with the same polymorphism derived genotypes and similar virulence gene profiles, provides evidence that similar strains are found in cattle and humans and transmission between the two species may occur.